CRYPTOGRAPHIC ANALYSIS OF THE SCHEME OF POLYLINEAR CRYPTOGRAPHY - Amirkhanova , D.; Mamyrbayev О. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
A group of unitriangular matrices is vulnerable to an attack based on the efficient method of computation of an unknown exponent m in a matrix equality A = Bm (solution of the discrete logarithm problem) in a group of one-dimensional matrices. We show that the system of the polylinear crypto raptly using nilpotent groups proposed by Kahrobaei et al. proves vulnerable.